Mycobacterium tuberculosis multi-drug-resistant strain M induces IL-17+IFNγ– CD4+ T cell expansion through an IL-23 and TGF-β-dependent mechanism in patients with MDR-TB tuberculosis. (2nd November 2016) - Basile, J I; Kviatcovsky, D; Romero, M M; Balboa, L; Monteserin, J; Ritacco, V; Lopez, B; Sabio y García, C; García, A; Vescovo, M; Montaner, P G; Palmero, D; et al.
Summary: We have reported previously that T cells from patients with multi-drug-resistant tuberculosis (MDR-TB) express high levels of interleukin (IL)-17 in response to the MDR strain M (Haarlem family) of Mycobacterium tuberculosis ( M. tuberculosis ). Herein, we explore the pathways involved in the induction of Th17 cells in MDR-TB patients and healthy tuberculin reactors [purified protein derivative healthy donors (PPD + HD)] by the M strain and the laboratory strain H37Rv. Our results show that IL-1β and IL-6 are crucial for the H37Rv and M-induced expansion of IL-17 + interferon (IFN)-γ – and IL-17 + IFN-γ + in CD4 + T cells from MDR-TB and PPD + HD. IL-23 plays an ambiguous role in T helper type 1 (Th1) and Th17 profiles: alone, IL-23 is responsible for M. tuberculosis -induced IL-17 and IFN-γ expression in CD4 + T cells from PPD + HD whereas, together with transforming growth factor (TGF-β), it promotes IL-17 + IFN-γ – expansion in MDR-TB. In fact, spontaneous and M. tuberculosis -induced TGF-β secretion is increased in cells from MDR-TB, the M strain being the highest inducer. Interestingly, Toll-like receptor (TLR)-2 signalling mediates the expansion of IL-17 + IFN-γ – cells and the enhancement of latency-associated protein (LAP) expression in CD14 + and CD4 + T cells from MDR-TB, which suggests that the M strain promotes IL-17 + IFN-γ – T cells through a strong TLR-2-dependent TGF-β production by antigen-presenting cells and CD4 + T cells. Finally, CD4 + T cells from MDR-TB patients infected with MDR Haarlem strains show higher IL-17 + IFN-γ – and lower IL-17 + IFN-γ + levels than LAM-infected patients. The present findings deepen our understanding of the role of IL-17 in MDR-TB and highlight the influence of the genetic background of the infecting M. tuberculosis strain on the ex-vivo Th17 response. Graphical Abstract: